Solving (x+5)(x+5) Using the Identity
This expression can be solved using the square of a binomial identity, which states:
(a + b)² = a² + 2ab + b²
Let's break down how to apply this to our problem:

Identify 'a' and 'b': In our expression, (x + 5)(x + 5), we can see that 'a' = x and 'b' = 5.

Apply the Identity: Using the identity, we substitute 'a' and 'b':
(x + 5)² = x² + 2(x)(5) + 5²

Simplify: Expanding the expression, we get:
(x + 5)² = x² + 10x + 25
Therefore, the solution of (x + 5)(x + 5) using the identity is x² + 10x + 25.
Note: This method is much faster and more efficient than expanding the expression directly by multiplying each term. It saves time and prevents potential errors.